Alkenones in the northwestern Mediterranean Sea - Marie-Alexandrine Sicre; Yann Ternois; Juan Carlos Miquel; Jean-Claude Marty (PANGAEA, 1999)
C37 alkenone fluxes were measured with sediment traps at 200 m depth over the years 1989/1990 and 1993/1994 to assess the interannual variability of the alkenone flux from the surface waters of the Mediterranean Sea. Fall and spring were identified as the high flux periods. SST estimates derived from the UK extquotesingle37 index indicated 50 m and 30 m as major production depths in spring and fall, respectively. Althought interannual variation of alkenone fluxes was notable, the seasonality and depth of production appeared to be recurrent features of the coccolithophorid cycle of production. Alkenone fluxes at 1000 m measured over the year 1993/1994 were about 5 times lower than at 200 m and show no evidence of preferential preservation relative to the organic carbon between these depths. SST predicted at 200 m and 1000 m indicated a remarkably good transfer of the surface temperature signal to deeper layers.
Supplement to: Sicre, M-A et al. (1999): Alkenones in the Northwestern Mediterranean sea: interannual variability and vertical transfer. Geophysical Research Letters, 26(12), 1735-1738, https://doi.org/10.1029/1999GL900353